The Implementation Effectiveness of the K3RS Program with Achievement of Compliance on Hospital Accreditation Standards at Dr. R. M. Djoelham Hospital in Binjai of 2019 - Melda Sari Tarigan; Gerry Silaba; Zulfendri (Britain International of Exact Sciences (BIoEx) Journal, 2020)
This study deals with the implementation effectiveness of the k3rs program with achievement of compliance on hospital accreditation standards in Dr. R. M. Djoelham Hospital in Binjai of 2019. This research was conducted at Dr. R. M. Djoelham Regional Hospital in Binjai City because the efforts in achieving accreditation have not been met in accordance with K3RS standards. Based on the results of the study it can be concluded that K3RS (Occupational Health and Safety) implementation in Dr. R. M. Djoelham Regional Hospitas of Binjai City based on category communication is good. This is indicated by despite the lack of budget in conducting socialization and simulation, but they continue to carry out socialization to related units, especially those with high risk with K3RS.